Business cycle convergence in EMU: A second look at the second moment - Jesús Crespo-Cuaresma; Octavio Fernández-Amador (University of Innsbruck, Department of Public Finance, 2010)
We analyse the dynamics of the standard deviation of demand shocks and of the demand component of GDP across countries in the European Monetary Union (EMU). This analysis allows us to evaluate the patterns of cyclical comovement in EMU and put them in contrast to the cyclical performance of the new members of the EU and other OECD countries. We use the methodology put forward in Crespo-Cuaresma and Fernández-Amador (2010), which makes use of sigma-convergence methods to identify synchronization patterns in business cycles. The Eurozone has converged to a stable lower level of dispersion across business cycles during the end of the 80s and the beginning of the 90s. The new EU members have also experienced a strong pattern of convergence from 1998 to 2005, when a strong divergence trend appears. An enlargement of the EMU to 22 members would not decrease its optimality as a currency area. There is evidence for some European idiosyncrasy as opposed to a world-wide comovement.
Keywords: E32; E63; F02; 330; Business cycle synchronization; structural VAR; demand shocks; European Monetary Union; Konjunkturzusammenhang; Europäische Wirtschafts- und Währungsunion; EU-Staaten